Factors affecting health-seeking behavior in sports climbers in Metro Manila: a cross-sectional study - Cruz, Danyelle Jay T.; Cabrera, Jan-Tyrone C. (Frontiers in Sports and Active Living, 2025)
IntroductionIn the Philippines, studies on athletes are hard to come by when compared to those done internationally, even more so on newer Olympic sports such as Sports climbing. Furthermore, there is a lack of internationally published research on professional health-seeking behavior for the physical conditions of Filipino athletes. Thus, the objective of the study was to investigate the characteristics of sports climbers in Metro Manila that were associated with better health-seeking behavior.Materials and methodsAn analytical cross-sectional study design was done using an online interview-assisted questionnaire. The Action-intention subscale of the Attitudes Towards Medical Help-seeking Scale was used to measure health-seeking behavior in the study population. Other data gathered includes the population characteristics, injury characteristics, and social-environmental characteristics of sports climbers in Metro Manila.ResultsA total of 125 participants were interviewed, majority of whom were young adults and middle aged (72.8%), college graduates (67.2%), working full time (54.4%), middle class (22.4%), with slightly more males (49.6%). None of the social-environmental factors were found to be significant (p > 0.05). Trust in websites was found to be the only significant personal factor (2.99 ± 1.00, p < 0.05). Among the injury factors studied, the location of pain at the hip/pelvis and knee was found to be significant (p < 0.05).DiscussionClimbers in Metro Manila have a decreased tendency to engage in health-seeking behavior. Because of this, sports climbers in Metro Manila may be a vulnerable group in terms of availability of health care systems specific to the sport, accessibility of knowledge for self-diagnosis and management, and data enough present in the Philippines to create guidelines and protocols for climbing injuries. Better monitoring of information on websites is needed. Healthcare providers should also improve the way they approach and deal with sport climbing injuries.